FAKTOR DETERMINAN PEMBERIAN IMUNISASI DASAR LENGKAP BALITA DI KECAMATAN PADARINCANG 2017 - THRESYA FEBRIANTI; Rusman Efendi (Dian Nuswantoro Semarang, 2019)
Immunization is one of the programs to control of infectious diseases, the coverage of immunization in Banten 2016 is still below the target of 90.26%. Coverage of UCI in subdistrict only reached 68.41% while Indonesia equal to 81,82%. This indicates the low coverage of UCI in the subdistrict area in Banten.The study aimed to analyze factors related to the completness of basic immunization in under-five children in Padarincang Sub-district in 2017. This study used case control design using secondary data and analyzed by Chi Square Test. The sample of this research is mother who has toddler with 66 cases and control of 66 people. The results showed that there was a significant correlation between family support with basic immunization completeness in underfive (p= 0,001; OR = 17,843 (95% CI = 2,271-140,223)), there was significant relation between house distance with basic immunization completeness in underfive (p= 0,002; OR = 5,304 (95% CI = 1,852-15,189)), and there was a significant relation between working mother with basic immunization completeness in toddler (p= 0,008; OR = 4,960 (95% CI = 1,559- 15,779)). It is expected that the Health Office will improve the provision of information about immunization to family members.